Combined effect of inorganic salts with calcium peroxide pretreatment for kenaf core biomass and their utilization for 2, 3-butanediol production. (June 2018) - Saratale, Rijuta Ganesh; Shin, Han Seung; Ghodake, Gajanan S.; Kumar, Gopalakrishnan; Oh, Min Kyu; Saratale, Ganesh Dattatraya
Graphical abstract: Highlights: Developed CaO2 pretreatment & optimized various operational parameters for KCP biomass. Addition of inorganic salts improved delignification, glucose yield and total sugar recovery. Maximum BDO production (10.42 g/L) was achieved using Klebsiella pneumoniae KMK05. This novel pretreatment strategy abstained loss of sugar components of biomass. Abstract: This study focuses on development of calcium peroxide (CaO2 ) pretreatment that removes major part of lignin but retaining most of sugar components of kenaf core powder (KCP) biomass. In chemical pretreatment, usually higher loss of biomass occurs which was less during this pretreatment strategy. Supplementation of inorganic salts; manganese sulfate (MnSO4 ) and cobalt chloride (COCl2 ) in CaO2 pretreatment resulted in maximum delignification of KCP relative to individual CaO2 pretreatment. Maximum glucose yield (98%) and hydrolysis yield (80.5%) was achieved after enzymatic hydrolysis (30 FPU/g of KCP) under optimized conditions. Analytical results proved effective lignin removal and significant destruction of KCP with this pretreatment strategy. Finally, utilization of KCP enzymatic hydrolysates by developed strain Klebsiella pneumoniae KMK05 resulted in maximum 2, 3-butanediol (BDO) production (10.42 g/L) and BDO titer (0.385 g/g of sugar). BDO titer achieved with KCP derived sugars were found comparable with the mixture of standard sugars which is notable.